A Novel Injectable Magnesium/Calcium Sulfate Hemihydrate Composite Cement for Bone Regeneration. (3rd June 2015) - Zhang, Shanchuan; Yang, Ke; Cui, Fuzhai; Jiang, Yi; E, Lingling; Xu, Baohua; Liu, Hongchen
Abstract : Objective. A novel injectable magnesium/calcium sulfate hemihydrate (Mg/CSH) composite with improved properties was reported here. Methods. Composition, setting time, injectability, compressive strength, and bioactivity in simulated body fluid (SBF) of the Mg/CSH composite were evaluated. Furthermore, the cellular responses of canine bone marrow stromal cells (cBMSCs) and bone formation capacity after the implantation of Mg/CSH in tibia defects of canine were investigated. Results. Mg/CSH possessed a prolonged setting time and markedly improved injectability and mechanical property p < 0.05 . Mg/CSH samples showed better degradability than CSH in SBF after 21 days of soaking p < 0.05 . Moreover, the degrees of cell attachment, proliferation, and capability of osteogenic differentiation on the Mg/CSH specimens were higher than those on CSH, without significant cytotoxicity and with the increased proliferation index, ALP activity, and expression levels of integrin β 1 and Coll I in cBMSCs p < 0.05 . Mg/CSH enhanced the efficiency of new bone formation at the tibia defect area, including the significantly elevated bone mineral density, bone area fraction, and Coll I expression level p < 0.05 . Conclusions. The results implied that this new injectable bone scaffold exhibited promising prospects for bone repair and had a great potential in bone tissue engineering.